Exploring innovation capabilities’ characteristics in low-tech firms - Benedet, Daniele Mello (2018)
The paper analyzes the innovation capabilities of low technology firms grounded on the “Innovation Capabilities Model”. This model divides the innovation capabilities in four: development, operations, management and transaction capability. The empirical analysis is based on two agribusiness firms located in Campos de Cima da Serra in Rio Grande do Sul / South of Brazil. Both firms present the four capabilities of the model, however, one capability is predominant in each firm: transaction and operations. The development capability was not a priority on these firms, as expected in low-technology firms, but it does not mean they do not have innovative routines. This broader approach to innovation, allowed to be captured by the model applied, contributes to complement existing studies on the complex nature of firms’ innovative process. The results also point to the necessity to make some reconsiderations about the model and apply it again in the low-tech context.